Riset pasar farmasi penjualan produk minyak aromaterapi - Soegiantoro, Didiek Hardiyanto (Poltekkes Kemenkes Kupang, 2024)
Aromatherapy medicated oil products have been used as complementary therapy in the treatment of disease. Currently, the number of aromatherapy medicated oil products is very diverse in terms of brands, sizes and packaging. To get an idea of ​​the influence of brand and packaging on the number of sales of this aromatherapy medicated oil product, market research was conducted at the ES Yogyakarta Pharmacy. This research is quantitative descriptive exploratory research using retrospective data. Population and sample of all aromatherapies medicated oil products available in pharmacies during 2023. The research results show that the best-selling medicated oil products are not determined by the first brand produced but are sold more by the brand that sells the most innovation and development of new products in aroma variants and packaging forms. Meanwhile, the packaging that people like most is roll-on packaging because it is more